Quality assurance in Saudi higher education: Transferability and policy implications for the Global South - Alghamdi, Musa; Ahmed, Syed Naeem; Rehman, Shafiq ur; Jack , Krista (Journal of International Students, 2026)
Over the past decade, Saudi Arabia has invested heavily in higher education reforms, positioning Quality Assurance (QA) as a central pillar of Vision 2030. This study investigates how these reforms are reshaping institutional practices while bureaucratic compliance cultures and the tensions between external accreditation models and local educational needs. Using a mixed-methods sequential explanatory design, survey data were collected from 248 faculty, administrators, and QA officers across four regions, complemented by 40 semi-structured interviews and systematic document analysis in two contrasting institutions. Findings show that QA is widely prioritized in strategic planning and leadership discourse, although faculty expressed greater skepticism than administrators. Leadership, technological integration, and faculty development emerged as key enablers, while resistance to change and bureaucratic compliance constrained innovation. Institutional documents demonstrated uneven alignment with Vision 2030 benchmarks, and cross-institutional comparisons revealed that the transferability of reforms depends on leadership style, institutional maturity, and faculty engagement.